An Experimental Study on the Performance Evaluation of Resistance Force and Impact-Sound in Reinforced Concrete Bearing-Wall Reinforced with Composite Mortar - Woung Ho, Seung; Joe Yoon, Seung; Seo, SooYeon (International Journal of Engineering and Technology, 2018)
The ultimate object of the study is developing new repair and strengthening method in order to reduce floor noise and improve seismic performance which are required at remodeling construction such as apartment house. Strength performance evaluation is conducted through cyclic behavior at the research of reinforced concrete wall applied composite mortar strengthening method with EVA and EPS. Also, research of impact-sound is conducted in the construction site for H apartment which are reinforced the same method. During the research, the strength performance fo the model reinforced EPS composite mortar is 1.19 times increased in comparison with unreinforced model and the model reinforced EVA composite mortar is 1.44 times increased.Â Â